Advancement of a Common Wheat (Triticum aestivum L.) Selection System - Tóth, Szilárd; Kovács Oskolás, Henriett (Acta Agraria Debreceniensis, 2006)
All the research in Hungary and other countries in Europe focus on improving the quality of crops and increasing the competitiveness of production. In this respect, we have to advance the conventional technological elements, reduce the application of pesticides and fertilizers, and produce new varieties suitable for environmentally-sound production. In our crop breeding programs, we applied conventional and biotechnological methods (embryo rescue and double haploid methods) in order to get somaclonal and gametoclonal variations. We produced winter wheat lines (HP-31-95, HP-82-96) by traditional way, which have high baking qualities and high nutrient efficiency. Some diseases can limit the quantity and quality of a wheat crop. We examined several wheat diseases in our winter wheat candidates, and we found that our progenies have resistance to leaf rust. With respect to a serious problem was the small quantity of applied fertilizers and the other externals, our research focused onto advance a common wheat selection system, with the help of it, we can handle these problems. We have summarized that our selected progenies can compete with the registered varieties with quality and environmental respect.